Evaluation of Cranial Base Morphology of Pakistani Population in Skeletal Class I, II and III Malocclusions - Alia, Faizan; Aziz, Rabia; Malik, Amna; Afzal, Hadiqa (Orthodontic Journal of Nepal, 2019)
Introduction: Cranial Base integrate different patterns of growth in various regions of the skull such as the nasal cavity, the oral cavity, and the pharynx. Anteroposterior jaw position is thought to be affected by cranial base growth. Although scientific literature shows conflicting results regarding both positive and negative correlation between the cranial base and skeletal malocclusions. Materials & Method: 138 patients selected according to the Inclusion criteria were divided into three major categories depending upon ANB angle. Class I, class II group and class III group. Pretreatment lateral cephalometric radiographs were taken. Linear and Angular measurements were measured. All the data was entered in SPSS version 25 and then analyzed by using descriptive statistics including mean, standard deviation and by using inferential statistics including Pearson correlation and ANOVA test. Result: No significant differences were recorded between cranial base deflection angles (N-S-Ar and N-S-Ba) and malocclusions groups while Anterior cranial base length S-N was found to be maximum in class III and posterior cranial base length S-Ba was greater in class I. Conclusion: Cranial base angles N-S-Ar and N-S-Ba did not demonstrate any statistically significant correlation with three malocclusion groups i.e. Class I, Class II and Class III and their correlation was negative.